Fiscal decentralization and natural hazard risks - Escaleras, Monica; Register, Charles A. (Public Choice, 2012)
At least to some extent due to pressure from international donors, many countries have become more fiscally decentralized the underlying premise being that greater decentralization might improve the provision of local public goods and services. We test this proposition by determining whether relatively more decentralized countries fare better when natural disasters strike in terms of its effects on the population. Overall, we find evidence supporting our maintained hypothesis, though the effect appears much more robust in developing countries.
MAG ID: 1965916064

Floods in future climates: a review - Whitfield, P.H. (Journal of Flood Risk Management, 2012)
Abstract At the global scale, the warming of the atmosphere will increase the capacity of the atmosphere to hold and accelerate the redistribution of water in the atmosphere. This suggests that flood‐generating processes linked to the atmosphere are likely to increase. However, the I ntergovernmental P anel on C limate C hange projections of future floods involve extremely complex issues that defy simple generalisations. Warming will alter other aspects of the water cycle increasing evaporation, changing precipitation patterns and intensity, and also affecting the processes involved in surface storage of water, including snowpack generation, snowmelt, river ice break‐up, and glacial melt. Many of these are active in flood generation, and changes may cause floods to decrease as well as increase. However, these processes take place not at the global scale but at relatively local scale, making generalisations about flooding in future climates difficult and uncertain. At the global scale, the role of land use is generally unresolved, but at a watershed scale, land‐use effects can be as important as changes in the meteorological processes. This review shows that while meteorologically driven flooding is expected to increase in a changed climate, making a precise pronouncement regarding all floods is unwise, as many types of floods will respond differently to changing climate and that because floods are watershed scale events, these local effects will remain important.
Keywords: Ouvrage_Collectif_Numéro1

Global exposure to river and coastal flooding: Long term trends and changes - Brenden Jongman; Jongman, Brenden; Philip J. Ward; Ward, Philip B.; Philip J. Ward; Ward, Philip J.; Jeroen C. J. H. Aerts; Aerts, Jeroen C. J. H. (Global Environmental Change-human and Policy Dimensions, 2012)
MAG ID: 2087805724

Les perspectives temporelles : les connaître pour en tenir compte dans nos interventions en promotion de la santé - Lessard, Lily (Global Health Promotion, 2012)
Résumé La modification des habitudes de vie pour adopter des comportements sains repose notamment sur la capacité des individus et des populations à estimer les conséquences à long terme des gestes accomplis aujourd’hui. Cette capacité peut cependant varier d’une personne à l’autre, notamment en raison des perspectives temporelles (PT) adoptées. Les PT réfèrent à la tendance d’une personne ou d’un groupe de personnes à orienter ses décisions en fonction d’une vision tournée vers le passé, le présent ou le futur. Cet article vise à démystifier le concept de PT et à comprendre leur construit, afin d’identifier différentes façons d’en tenir compte dans les interventions en promotion de la santé. L’influence des PT sur la santé est principalement liée à leur capacité d’agir sur la motivation des personnes à adopter et à maintenir certains comportements. Une attention particulière doit être portée aux personnes et aux populations dont les PT sont orientées vers le présent. Elles présenteraient un plus grand risque d’adopter des comportements délétères et seraient susceptibles d’être moins sensibles aux messages qui visent la modification de ces comportements que les personnes qui adoptent une PT orientée vers le futur. En ce qui concerne leur construit, les PT sont le fruit de différentes dynamiques psychologiques et des facteurs individuels (âge, sexe, état de santé) et environnementaux (milieu familial, statut socioéconomique, éducation, culture). Parmi les moyens présentés pour tenir compte des PT dans les interventions en promotion de la santé figurent la mise en valeur des avantages à court terme d’un changement de comportement qui vise des bénéfices à long terme pour la santé, la modulation de l’intensité du soutien à l’empowerment des communautés en fonction des PT adoptées et la permutation d’une PT orientée vers le présent vers une PT orientée vers le futur.
Keywords: Lessard_Lily

An Exploration of the Link between Development, Economic Growth,and Natural Risk - Hallegatte, Stephane (2012)
This paper investigates the link between development, economic growth, and the economic losses from natural disasters in a general analytical framework, with an illustration on hurricane flood risks in New Orleans. It concludes that, where capital accumulates through increased density of capital at risk in a given area, (i) the probability of disaster occurrence decreases with income; (ii) capital at risk and thus economic losses in case of disaster – increases faster than economic growth; (iii) increasing risk-taking reinforces economic growth. Economic growth and improved protection transfer risks from frequent low-intensity events to rarer high-impact events. In this context, average annual losses from disasters grow with income, and they grow faster than income at low levels of development and slower than income at high levels of development. These findings are robust to a broad range of modeling choices and parameter values, to the inclusion of risk aversion, and to variations in the decision-making framework (including the introduction of prospect theory's decision weights, biases in risk perception and myopic expectations). They show that risk-taking is both a driver and a consequence of economic development, that risk taking should not be indiscriminately suppressed, and that the world is very likely to experience fewer but more costly disasters in the future.
MAG ID: 1808689159

Managing the Risks of Extreme Events and Disasters to Advance Climate Change Adaptation, A Special Report of Working Groups I and II of the Intergovernmental Panel on Climate Change - Intergovernmental Panel on Climate Change (IPCC) (Cambridge University Press, 2012)
Keywords: Ouvrage_Collectif_Numéro1

Determinants of Risk: Exposure and Vulnerability - Cardona, Omar-Dario; Van Aalst, Maarten K.; Birkmann, Jörn; Fordham, Maureen; McGregor, Glenn; Perez, Rosa; Pulwarty, Roger S.; Schipper, E. Lisa F.; Sinh, Bach Tan; Décamps, Henri; Keim, Mark; Davis, Ian; et al. (Managing the Risks of Extreme Events and Disasters to Advance Climate Change Adaptation, 2012)
Keywords: Ouvrage_Collectif_Numéro1